2020
DOI: 10.1177/1010428320925301
|View full text |Cite
|
Sign up to set email alerts
|

ΔKi67 proliferation index as independent predictive and prognostic factor of outcome in luminal breast cancer: data from neoadjuvant letrozole-based treatment

Abstract: A key tool for monitoring breast cancer patients under neoadjuvant treatment is the identification of reliable predictive markers. Ki67 has been identified as a prognostic and predictive marker in ER-positive breast cancer. Ninety ER-positive, HER2 negative locally advanced breast cancer patients received letrozole (2.5 mg daily) and cyclophosphamide (50 mg daily) with/without Sorafenib (400 mg/bid daily) for 6 months before undergoing surgery. Ki67 expression and tumor size measured with caliber were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Ki67 is considered to be a prognostic and predictive indicator of ER-positive BC, and can be used to predict disease-free and overall survival in BC patients treated with neoadjuvant endocrine therapy. 9 The molecular classification of BC is thus generally based on the single or multiple expressions of HER2, ER, PR, and Ki67. The different biological behaviors and prognoses of different subtypes of BC demonstrate the need to adjust the therapeutic strategies according to the BC subtype.…”
mentioning
confidence: 99%
“…Ki67 is considered to be a prognostic and predictive indicator of ER-positive BC, and can be used to predict disease-free and overall survival in BC patients treated with neoadjuvant endocrine therapy. 9 The molecular classification of BC is thus generally based on the single or multiple expressions of HER2, ER, PR, and Ki67. The different biological behaviors and prognoses of different subtypes of BC demonstrate the need to adjust the therapeutic strategies according to the BC subtype.…”
mentioning
confidence: 99%
“…Some studies only find significant Ki67 proliferation index differences when comparing pre-NAC with post-surgery in Luminal subtypes [ 37 , 38 ] while other studies have demonstrated that Ki67 reduction also plays a role in TN breast cancer [ 39 , 40 ]. While a separate investigation mentioned , it only discussed its prognostic role and predictive value within 90 Luminal subtype patients with neoadjuvant letrozole-based treatment without classifying it more broadly [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicates that Ki67 levels pre-NAC can be an independent prognostic predictor for OS and DFS [ 12 , 16 ]. Endocrine therapy can decrease cell proliferation, presenting as changed Ki67 level pre- and post-NAC [ 20 , 21 ]. In the POETIC clinical phase-3 trial, this change in Ki67 levels was able to guide endocrine therapy decisions for women with ER-positive breast cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, results from the MADONNA study, a multicenter, double-blind, phase II study, revealed a lack of survival advantage upon the addition of sorafenib to docetaxel as first-line treatment in breast cancer patients with metastatic or locally advanced HER2-negative disease (Mavratzas et al, 2019). Recently, Ianza et al showed no difference in survival outcomes for adding sorafenib to letrozole and cyclophosphamide in postmenopausal patients with locally advanced estrogen receptor (ER)-positive, HER2-negative breast cancer in a phase III trial (Ianza et al, 2020). Interestingly, a higher percentage of patients on sorafenib treatment had disease progression (Ianza et al, 2020).…”
Section: Sorafenibmentioning
confidence: 99%
“…Recently, Ianza et al showed no difference in survival outcomes for adding sorafenib to letrozole and cyclophosphamide in postmenopausal patients with locally advanced estrogen receptor (ER)-positive, HER2-negative breast cancer in a phase III trial (Ianza et al, 2020). Interestingly, a higher percentage of patients on sorafenib treatment had disease progression (Ianza et al, 2020). Other clinical studies have constantly supported a lack of survival advantage for the combination of sorafenib and chemotherapy in patients with advanced breast cancer (Gradishar et al, 2013;Luu et al, 2014;Yardley et al, 2016a).…”
Section: Sorafenibmentioning
confidence: 99%